Designing English Coursebook for Islamic Bilingual Boarding School Based on the Value of the Four Pillars of Nationality - Mahmud, Mahmud; Linda, Linda (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
The purpose of this study is to develop an English course book for bilingual boarding school (Pesantren). The value of four of national pillars (Pancasila, Bhineka Tunggal Ika, UUD 45 and NKRI) is chosen as the theme of the course book. The research model uses research and development (R&D) methods of Reiser and Mollenda where the development model has several steps, namely: Analysis, Design, Development, Implementation and Evaluation (ADDIE). The 45 students were taken as the subject of the research and determined as purposive research sample from 300 populations of all students. The instruments of this research were test and questionnaire. The descriptive and quantitative analyses were employed in this research.The result of this research is an English book which designed by some consideration; the curriculum is adapted from general English, the sequence and approach of the coursebook is adapted from coursebook the model by Joko Priyana, Riandi and Anita P., and every chapter of the book contains certain information and the value of the four pillars of nationality.